Exploring Mobile/WiFi Handover with Multipath TCP - Ay, Gokhan; Doğanalp, Neşet; Elbousiffi, Ans Mohamed (Eastern Mediterranean University (EMU), Famagusta /North Cyprus, 2015)
The everlasting fact that data traffic always increases due to the expanding number of subscribers. Users always want to have a fast and reliable network speeds. As this growth in demand led data traffic to increase, operators started dedicating their work on some new and efficient ways that is different from 3G or 4G networks,one idea has been considered here offloading to Wi-Fi. Multipath TCP (MPTCP) which is an evolution of TCP that allows the simultaneous use of multiple interfaces for a single connection while standard TCP is kept the same for socket API to application. Multipath TCP allows to smooth handover from WiFi to 3G back and forth.In our experiment,we observe the workability of MPTCP over real WiFi / 3G or 4G networks and use our linux kernel implementation of Multipath TCP that results in smooth handover without lose of data.We observe that Multipath TCP energy consumption and performance depends on the modes of the kernel by performing perfect results in applications such as VoIP.
Undergraduate Project Report submitted in partial fulfillment of the requirements for the degree of Bachelor of Science (B.S.) in Electrical and Electronic Engineering Department Eastern Mediterranean University June 2015.Supervisor:Prof. Dr. Hasan AMCA
Keywords: Multipath TCP; Join capability; HMAC; Middlebox; 3G; 4G; Handover